Canine pyometra – an update and revision of diagnostic terminology - Santana, Clarissa Helena; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2021)
Pyometra is frequently diagnosed in female dogs, and it is characterized by endometrial inflammation, accumulationof purulent exudate within the lumen, and bacterial infection. In the dog, pyometra affects more often aged nulliparousbitches during the luteal phase. Pathogenesis of pyometra is multifactorial and progesterone seems to be a key factor. Cysticendometrial hyperplasia has been described as a predisposing condition for canine pyometra. However, a recent studydemonstrated that cystic endometrial hyperplasia is not significantly associated with naturally occurring pyometra, whereasthere is a significant association of this condition with pseudoplacentational endometrial hyperplasia. The aim of this reviewis to provide an update on canine pyometra, with focus on its association with uterine hyperplasic lesions, which supports aproposal for adoption of more adequate diagnostic terminology.